Mechanism(s) of Toxic Action of Zn2+ and Selenite: A Study on AS-30D Hepatoma Cells and Isolated Mitochondria - Elena A. Belyaeva; Nils-Erik L. Saris (Biochemistry Research International)
Mitochondria of AS-30D rat ascites hepatoma cells are found to be the main target for Zn2+ and sodium selenite (Na2SeO3). High [mu]M concentrations of Zn2+ or selenite were strongly cytotoxic, killing the AS-30D cells by both apoptotic and necrotic ways. Both Zn2+ and selenite produced strong changes in intracellular generation of reactive oxygen species (ROS) and the mitochondrial dysfunction via the mitochondrial electron transport chain (mtETC) disturbance, the membrane potential dissipation, and the mitochondrial permeability transition pore opening. The significant distinctions in toxic action of Zn2+ and selenite on AS-30D cells were found. Selenite induced a much higher intracellular ROS level (the early event) compared to Zn2+ but a lower membrane potential loss and a lower decrease of the uncoupled respiration rate of the cells, whereas the mtETC disturbance was the early and critical event in the mechanism of Zn2+ cytotoxicity. Sequences of events manifested in the mitochondrial dysfunction produced by the metal/metalloid under test are compared with those obtained earlier for Cd2+, Hg2+, and Cu2+ on the same model system.